Temperature measurement & control - Leigh, J. R. (James R.) (London P. Peregrinus on behalf of the Institution of Electrical Engineers, 1988)
The book reviews developments in the following areas: temperature measurement; thermocouple; resistance thermometer; thermistors; radiation thermometry; temperature sensors; industrial temperature measurement problem; heat sources; temperature control and energy conservation.
Keywords: Temperature measurements; Temperature measuring instruments; Temperature control; Electronic books